Pelayanan Publik di Kecamatan Purwakarta Kota Cilegon Berdasarkan Tata Kelola Taat Asas - Saepudin, Eli Apud; Laksana, April; Wahyiah, Ita Rosita (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
Services to the community based on the principles of governance refer to prioritizing the general public, meaning that every service that the community wants should not be linked to personal affairs must be professionalism at work, rights and obligations are a guarantee of the realization of the legal certainty of service providers, togetherness of the general public regardless of customs, race, ethnicity, language, religion, class, gender, and economic status, the balance of rights and obligations of the community is to comply with the rules that have been agreed upon together. To meet the needs of the community for administration, it has been provided by Purwakarta sub-district employees who are ready to provide guidance and direction to their citizens in meeting administrative needs to make identity cards, certificates of incapacity, marriage cover letters, business premises licenses, submitting land certificates, permits to install billboards and many more administrative activities in the Purwakarta sub-district of Cilegon city have a motto of excellent service is our priority and we are servants of the state serving the community.